ANALISIS SENI KALIGRAFI ARAB DALAM PENGEMBANGAN INDUSTRI KREATIF BERBASIS EKONOMI SYARI’AH - M. Dzaki Sholihin; Siti Aisya Rambe (Yayasan Haiah Nusratul Islam, 2025)
This research identifies the potential of calligraphy art in the creative industry through its aesthetic value and spiritual meaning. By applying sharia economic principles—fairness, transparency, and sustainability—this study designs an ethical and sustainable business model for the development of calligraphy art. In addition, this research explores the opportunities and challenges of the calligraphy industry, such as the global market, technological innovation, as well as capital requirements and competition. Design innovation and digital media are the keys to maintaining the relevance of this art in the modern era. Using qualitative methods and literature studies, the research results show that Arabic calligraphy art can become a leading sector of creative industries based on a fair and sustainable sharia economy.